ANALISIS KANDUNGAN (AIR, ABU, DAN LOGAM BERAT) PADA KOPI BUBUK ASAL GAYO - bhayu gita bhernama (Pusbindiklat - LIPI, 2019)
Gayo coffee is one type of arabica coffee originating from the Gayo plateau, Central Aceh district. Where Gayo coffee has a distinctive flavor, strong aroma and taste specifically. In the Gayo coffee processing process, it is inseparable from various kinds of contamination, so analysis needs to be done. Analysis was carried out on two coffee samples taken from two factories, namely factories A and B. Analysis carried out included analysis of water, ash, and metal content of ground coffee originating from Gayo. The analysis of metal content was carried out by using Atomic Absorbtion Spectroscopy (AAS). The test results showed that coffee A had a water content of 0.0397% and ash content 4% while coffee B had a water content of 0.01772% and ash content 4.3%. The test results of heavy metal within coffee A and B revealed that the contaminants of Cu, Hg, Pb and Zn metals existed. The coffee A contained Cu and Hg metal contamination with levels of 6.4945 and 0.0029 mg/Kg respectively. While, the coffee B contained Cu and Hg metal contamination with levels of 7.6120 and 0.0042 mg/Kg, respectively. The contamination of Pb and Zn within the coffee A and B were low and insignificant (0.001 mg/Kg). From the results of the analysis, it was found that the water, ash and metal content in coffee A and coffee B complies to the Indonesian National Standards (SNI) 01-3542-2004.